Engaging the Mechanisms of Faith? - Selina Palm; Carola Eyber (The Thinker)
Violence against children is shaped by social norms which are frequently underpinned by faith-related beliefs and values. There is renewed global recognition of the role of religions in legitimating or challenging harmful attitudes and practices, and this highlights the relevance and influence of faith communities in child protection. Faith communities may also have a unique role to play by engaging spiritual capital and faith mechanisms for positive change. These approaches go beyond an instrumentalised yet important role in service provision alone, to also transform harmful beliefs and offer positive alternatives grounded in faith mandates. This article draws on insights from a 2019 scoping study that explored positive and negative beliefs across multiple faith traditions that shape the perpetration, justification, or engagement to end violence against children. The study included three research components: a literature review, a case study submission process, and key informant interviews with experts on child violence working with diverse faith communities. Its findings show many ways in which religion’s spiritual capital can either help place children at society’s centre or can support harmful hierarchies of power that enable violence against children and seek to resist positive change.